An Error Analysis of Imla’iyyah in Arabic Speech Text Writing: A Case Study from an Inter-School Competition - Putra Hardiansyah; M. Syihabul Ihsan Al Haqiqy; Ngantori Ngantori; Asbarin Asbarin; Nur Halifah (Lembaga Ta'lif wa An-Nasyr (LTN) PBNU, 2025)
Errors in writing speech texts reflect a lack of understanding of IMLA rules and can affect the quality of the delivered speech. This study aims to describe the types of imla’iyyah errors and evaluate their occurrence in the writing of Arabic speech texts at PORSENI (Sports and Arts Week) at KKMT 01 Gresik in 2025. This research employs a qualitative method with an analytical study type through the imla’ approach. Documentation was used as the data collection method, with 31 speech texts obtained from Google Drive serving as the primary data source. The data analysis technique follows Corder’s theory, which includes collecting error data, identifying and classifying errors, and explaining and evaluating them. The results of this study are: (1) errors in writing hamzah washal and qatha’ occurred 32 times (52%), errors in the addition of the letter “al” were found 15 times (24%), errors in writing mad occurred 6 times (9%), errors in adding and omitting letters were found 5 times (8%), letter substitution errors occurred once (2%), and letter connection errors occurred 3 times (5%). (2) The suggested evaluation includes improving understanding of imla’ rules, increasing practice in writing and spelling words correctly, comprehending and applying mad writing rules properly, and enhancing typing skills.